Gender‐related differences in treatment and outcome of extracorporeal cardiopulmonary resuscitation‐patients. Issue 5 (15th December 2020) - Gaisendrees, Christopher; Djordjevic, Ilija; Sabashnikov, Anton; Adler, Christoph; Eghbalzadeh, Kaveh; Ivanov, Borko; Walter, Sebastian G.; Braumann, Simon; Wörmann, Jonas; Suhr, Laura; Gerfer, Stephen; Baldus, Stephan; et al.
Abstract: Extracorporeal cardiopulmonary resuscitation (eCPR) is a rapidly growing treatment strategy due to significant improvement in selected patients' survival rates. Gender‐related differences might impact the outcome of therapeutic measures. Therefore, we sought to investigate patients with eCPR at our interdisciplinary extracorporeal membrane oxygenation center regarding sex‐related differences with the view to potentially adjusting current selection criteria. From January 2016 to December 2019, 71 patients underwent eCPR at our institution. Data before eCPR and early outcome parameters were analyzed comparing male and female patients. The cohort analyzed consisted of 60 male (84%) and 11 female (15%) patients. Comparing both groups, male patients significantly more frequently suffered out‐of‐hospital cardiac arrest (68% male vs. 36% female, P = .04), whereas female patients were associated with more in‐hospital cardiac arrest (32% male vs. 64% female, P = .04). Creatinine levels differed significantly (1.5 (1.1;2.1) mg/dL in male vs. 1.0 (0.7;1.5) mg/dL in female patients, P = .03). Also, several hepatic parameters showed a significant difference between the groups: aspartate aminotransferase 423 (249;804) U/L in male vs. 115 (61;408) U/L in female patients, P = .01; alanine aminotransferase 174 (102;446) U/L in male vs. 86 (36;118) U/L in female patients, P = .01). Renal failure requiring hemodialysis occurred more frequently in men than in women ( P < .01). There is a significant effect of male sex regarding renal failure with subsequent continuous venovenous hemodialysis (CVVH) ( R 2 = 0.11, ANOVA P = .01, 95% CI = −0.79‐−0.079). However, in‐hospital mortality was comparable between the groups (78% in male vs. 72% in female patients, P = .68). Our retrospective study showed several gender‐related differences associated with different cardiac arrest scenarios. Male sex was associated with a significantly higher risk for renal failure requiring CVVH. Survival rates were comparable between the groups. Further investigations should include gender in the evaluation of risk stratification for eCPR‐related complications to further improve selection criteria for this demanding therapy. Abstract : In this retrospective analysis of eCPR patients, male sex was associated with a significantly higher risk for renal failure requiring CVVH. There were no significant differences in Survival between genders.